KOEFISIEN PEMADAMAN TAJUK DAN EFISIENSI PENGGUNAAN RADIASI SURYA PADA TANAMAN KENTANG (Solanum tuberosum L.) VARIETAS GRANOLA DI GALUDRA, CIANJUR, JAWA BARATCANOPY EXTINCTION COEFFICIENT AND SOLAR RADIATION USE EFFICIENCY... - I. Handoko; Titik Kodarsih; A. Ariyani (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2010)
Important climatic factor affecting growth of potato crop other than temperature is the availability of solar energi. Growth of the crop can be predicted from the amount of intercepted solar radiation by crop canopy, however, climatological station only measures incoming solar radiation above crop canopy (Qo). This experiment aims to derive parameter of canopy extinction coefficient (k) that is required to calculate intercepted radiation based on Qo; and parameter of radiation-use efficiency (ε) to calculate crop biomass based on that intercepted radiation. This research found the value of k increasing from k=0.15 to k=0.50 associated with increasing LAI from 0.98 to 1.98. Solar radiation use efficiencies that were calculated based on above-ground biomass (AGB) and total biomass (AGB+tuber) are respectly εand εTotal=4,49 g MJ-1. Important climatic factor affecting growth of potato crop other than temperature is the availability of solar energi. Growth of the crop can be predicted from the amount of intercepted solar radiation by crop canopy, however, climatological station only measures incoming solar radiation above crop canopy (Qo). This experiment aims to derive parameter of canopy extinction coefficient (k) that is required to calculate intercepted radiation based on Qo; and parameter of radiation-use efficiency (ε) to calculate crop biomass based on that intercepted radiation. This research found the value of k increasing from k=0.15 to k=0.50 associated with increasing LAI from 0.98 to 1.98. Solar radiation use efficiencies that were calculated based on above-ground biomass (AGB) and total biomass (AGB+tuber) are respectly εand εTotal=4,49 g MJ-1.